Cardiac autonomic function and hot flashes among perimenopausal and postmenopausal women. Issue 7 (July 2017) - Gibson, Carolyn J.; Mendes, Wendy Berry; Schembri, Michael; Grady, Deborah; Huang, Alison J.
Abstract: Objective: Abnormalities in autonomic function are posited to play a pathophysiologic role in menopausal hot flashes. We examined relationships between resting cardiac autonomic activity and hot flashes in perimenopausal and postmenopausal women. Methods: Autonomic function was assessed at baseline and 12 weeks among perimenopausal and postmenopausal women (n = 121, mean age 53 years) in a randomized trial of slow-paced respiration for hot flashes. Pre-ejection period (PEP), a marker of sympathetic activation, was measured with impedance cardiography. Respiratory sinus arrhythmia (RSA), a marker of parasympathetic activation, was measured with electrocardiography. Participants self-reported hot flash frequency and severity in 7-day symptom diaries. Analysis of covariance models were used to relate autonomic function and hot flash frequency and severity at baseline, and to relate changes in autonomic function to changes in hot flash frequency and severity over 12 weeks, adjusting for age, body mass index, and intervention assignment. Results: PEP was not associated with hot flash frequency or severity at baseline or over 12 weeks ( P > 0.05 for all). In contrast, there was a trend toward greater frequency of moderate-to-severe hot flashes with higher RSA at baseline ( β = 0.43, P = 0.06), and a positive association between change in RSA and change in frequency of moderate-to-severe hot flashes over 12 weeks ( β = 0.63, P = 0.04). Conclusions: Among perimenopausal and postmenopausal women with hot flashes, variations in hot flash frequency and severity were not explained by variations in resting sympathetic activation. Greater parasympathetic activation was associated with more frequent moderate-to-severe hot flashes, which may reflect increased sensitivity to perceiving hot flashes.